Characterization of Cebu province municipalities using probabilistic seismic hazard assessment (PSHA) and geographic information system (GIS) - Uy, Erica Elice S. (Animo Repository, 2020)
Cebu province is considered to be one of the most developed provinces in the Philippines with 2.94 Million population. Last October 2013, a Magnitude of 7.2 earthquake affected the province and left a death toll of 222. Many of the cultural heritage structures were affected, and with this it is important that seismic assessment is performed for the province of Cebu. Information regarding its vulnerability to earthquake damages is needed to lessen the casualties. In this study the structures were assessed though Probabilistic Seismic Hazard Assessment and thoroughly characterized qualitatively according to Low, Medium and High Priority by Geographic Information System (GIS). These characterizations may be used as basis for seismic provisions in building codes, budget allocations for risk reduction and for risk models. © Published under licence by IOP Publishing Ltd.